PERBANDINGAN ANTARA PEMIKIRAN KARL MARX DENGAN PEMIKIRAN J. KRISHNAMURTI TENTANG PERUBAHAN SOSIAL - Ari Basuki (Humaniora, 2008)
Social change is definite. The question is how soon it will take place, whether it will go in a positive or negative direction, and in what mode it will happen. Karl Marx believed that a new society is created through a social revolution. On the contrary, J. Krishnamurti proposed an inward revolution. It is interesting to compare these two ideas. Marx said that contradiction between the powers of production will provoke a social revolution. As for Krishnamurti, a social revolution without altering the soul will not alter human suffering. Which is prominent: social revolution or inward revolution? Valuable inspirations can be gained from comparing the two.